FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN PASIEN HEMODIALISA DI RSU HKBP BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2018 - Manurung, Melva (Jurnal Keperawatan Priority, 2018)
The process of hemodialysis in the hospital can cause anxiety and physical disturbing the neurological system such as weakness, fatigue, anxiety, decreased concentration. Some of the factors that affect the anxiety of hemodialysis patients are age, sex, education level, treatment experience, length of therapy, financing, family motivation. This study aims to analyze the factors that affect the anxiety level of hemodialysis patients in HKBP Balige Hospital. The design used in this study is descriptive "cross sectional", which became the population in this study was a patient with renal failure who underwent hemodialysis at HKBP Balige Hospital. The sample of this research is 22 hemodialysis patients by doing purposive sampling. The instrument used in the demographic data questionnaire, this section consists of the Spielberger et al. (1983) State Trait Anxiety Inventory (STAI) and Atrait and family motivation questionnaires. Test the hypothesis by using Spearman correlation. Based on data analysis, obtained before the Hemodialisa (State Anxiety Inventory), the anxiety of patients experienced moderate anxiety as many as 12 people (54.5%) and heavy ansietas as many as 10 people (45.5%). At the time of hemodialysis (Trait Anxiety Inventory) patients experienced moderate anxiety as many as 14 people (63.6%), heavy anxiety as many as 8 people (36.4%). Based on the results of statistical tests it is known that there is no effect of age on patient anxiety before and during hemodialysis. There was no influence of sex on patient anxiety before and during hemodialysis. There was no effect of patient education level with patient's anxiety before and during hemodialysis. There was no effect of patient treatment experience with patient anxiety before and during hemodialysis. There was a long-standing effect of patient therapy with anxiety before the hemodialysis patient and no long-term therapy effects on patient anxiety during hemodialysis. There was no effect of patient treatment financing with patient anxiety before and during hemodialysis. There was no influence of family motivation of patients with patient anxiety before and during hemodialysis at HKBP Balige Hospital. It is expected that the hospital will improve the nursing service especially in the hemodialysis room, through providing holistic bio-psycho-social nursing care in patients with kidney failure so as to reduce anxiety, increase the life expectancy of patients with renal failure who undergo hemodialysis. The hospital needs to improve the human resources, especially the nurse of hemodialysis through continuing education, the latest training on nursing science and the training of nurse competence improvement.